2018
DOI: 10.3390/jof4010028
|View full text |Cite
|
Sign up to set email alerts
|

PS, It’s Complicated: The Roles of Phosphatidylserine and Phosphatidylethanolamine in the Pathogenesis of Candida albicans and Other Microbial Pathogens

Abstract: Abstract:The phospholipids phosphatidylserine (PS) and phosphatidylethanolamine (PE) play important roles in the virulence of Candida albicans and loss of PS synthesis or synthesis of PE from PS (PS decarboxylase) severely compromises virulence in C. albicans in a mouse model of systemic candidiasis. This review discusses synthesis of PE and PS in C. albicans and mechanisms by which these lipids impact virulence in this fungus. This is further compared to how PS and PE synthesis impact virulence in other fungi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 110 publications
(131 reference statements)
0
37
0
Order By: Relevance
“…One related peptide exhibits antifungal activity against Candida albicans and Trichosporon beigelii [ 40 ]. It should be noted that PS plays a relevant role in both cancer development [ 35 , 41 , 42 , 43 ] and Candida albicans virulence [ 44 , 45 , 46 , 47 , 48 ] for which PG [ 49 ] and PI [ 47 ] are also important.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One related peptide exhibits antifungal activity against Candida albicans and Trichosporon beigelii [ 40 ]. It should be noted that PS plays a relevant role in both cancer development [ 35 , 41 , 42 , 43 ] and Candida albicans virulence [ 44 , 45 , 46 , 47 , 48 ] for which PG [ 49 ] and PI [ 47 ] are also important.…”
Section: Resultsmentioning
confidence: 99%
“…One member of the K11 SR family also displays activity against fungi like Candida albicans . As shown in this work, K11 targets PS and PI, both being relevant for Candida virulence [ 44 , 45 , 46 , 47 , 48 ], together with PG [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…PS synthase (⑩), PS decarboxylase (⑪), and phospholipid methylase (⑬), shown with bold arrows in Figure 3 , have been reported in the literature as potential antifungal targets [ 32 ]. The Candida albicans PS synthase mutant, Δ cho1 , lacking PS, has a decreased PE content and is avirulent in a mouse model of systemic candidiasis.…”
Section: Specific Lipid Metabolism In Fungimentioning
confidence: 99%
“…The cho1⌬/cho1⌬ null mutant is also viable in C. albicans (15). Interestingly, although the in vitro growth of this mutant can be rescued by addition of ethanolamine, Cho1 is essential for Candida virulence in a murine infection model and has thus been proposed as a potential drug target (15,33). A recent study further demonstrated that the mutant cells might not be able to acquire sufficient ethanolamine from the host, leading to the avirulent phenotype (34).…”
Section: Discussionmentioning
confidence: 99%